First record of insect-plant interaction in Late Cretaceous fossils from Nelson Island (South Shetland Islands Archipelago), Antarctica - EDILSON B. DOS SANTOS FILHO; ARTHUR S. BRUM; GEOVANE A. DE SOUZA; RODRIGO G. FIGUEIREDO; CRISTIAN D. USMA; JOÃO HENRIQUE Z. RICETTI; CRISTINE TREVISAN; MARCELO LEPPE; JULIANA M. SAYÃO; FLAVIANA J. LIMA; GUSTAVO R. OLIVEIRA; ALEXANDER W.A. KELLNER (Anais da Academia Brasileira de Ciências, 2023)
Abstract Despite the enormous paleobotanical record on different islands of the Antarctic Peninsula, the evidence of insect activity associated with fossilized plants is scarce. Here we report the first evidence of insect-plant interaction from Cretaceous deposits, more precisely from a new locality at the Rip Point area, Nelson Island (Antarctic Peninsula). The macrofossil assemblage includes isolated Nothofagus sp. leaf impressions, a common component of the Antarctic paleoflora. Two hundred leaves were examined, of which 15 showed evidence of insect activity, displaying variations in size, shape, and preservation. Two types of interaction damage, galls and mines, were identified. A single specimen retained a circular scar recognized as galling scar, while meandering tracks were considered mines. These traces of herbivore insect activity, correspond to the oldest known record of this type of interaction of West Antarctica and the oldest record of insect-plant interaction in Nothofagus sp. reported so far.